PATRIOTISMO E NACIONALISMO NO FRONT INTERNO: OS DISCURSOS DO JORNAL DIÁRIO DOS CAMPOS ACERCA DA SEGUNDA GUERRA MUNDIAL (PONTA GROSSA- 1942 E 1944) - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
During the Brazilian participation in World War II (1939 – 1945), the press of the country tended to publish nationalist and patriotic texts, sharing some principles that were seen as necessary to an alignment of society. In the publications of the daily newspaper Diário dos Campos it is presented a speech that aimed to encourage the population of the city of Ponta Grossa to share feelings and patriotic actions as a way to contribute to the victory of the country and its allies. Facing these facts, this research sought to analyze the approach of some matters that refer to the relation between Brazil and World War II, which appears in the editions of the newspaper. It also pursued to analyze the appeal that these discourses made to the society, as well as the embracing of some attitudes and behaviors that were considered civic in the period from 1942 to 1944. Thus, it is attempted here to investigate how the speech presented by this newspaper represents the events and ideologies at the time, not only in Brazil but also in an international context and in a perspective towards the local population. Searching this, and facing the analysis of the speech, this research consisted of the review of the bibliography that corresponded to the mentioned period of time, specially about the Brazilian participation in the conflict, besides studies about general characteristics of the local society, which was consumer of the concerned newspaper.
Keywords: discurso; Segunda Guerra Mundial; Ponta Grossa; imprensa escrita; Diário dos Campos; speech; World War II; Ponta Grossa; written press; Diário dos Campos; CNPQ::CIENCIAS HUMANAS::HISTORIA